Morphological and syntactical irregularities in the Book of Revelation : a Greek hypothesis - Moț, Laurențiu Florentin. (Linguistic Biblical Studies, 2015)
Morphological and Syntactical Irregularities in the Book of Revelation by Laurențiu Florentin Moț is an approach to the solecisms of Johannine Apocalypse from a Greek perspective. The work aims at demonstrating that, in accord with Second Language Acquisition studies, Semitic transfer in Revelation is extremely rare. Most of its linguistic peculiarities can be explained within the context of the Greek language. Morphological and Syntactical Irregularities in the Book of Revelation is unique in several ways. First, it deals with the most comprehensive list of solecisms. Second, it treats grammatical irregularities in their own right, looking at their cause, explanation, and contribution to the interpretation of the text. Third, it is interdisciplinary, bringing together textual criticism, Greek linguistics, and NT exegesis.